2020
DOI: 10.32628/cseit206619
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of A Digital PID/LQR Control System for Duty-Cycle Modulation Buck Converters

Abstract: <p>This research paper presents a synthesis approach of a digital optimal PID/LQR control system for DCM (duty-cycle cycle modulation) Buck converters. The step response of the DCM Buck converter is obtained under Multisim virtual simulation framework. The related data file is saved as *.SCP format, and imported into EditPad Lite7 editor, then exported as Matlab file to be processed. The transfer function of the DCM Buck converter is computed from the imported step response data. Then, using the zoh (zer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Thus, we showed that the strength of the control could be significantly reduced by applying a perturbation with a phase difference between the perturbing signal and the sawtooth signal. Moreover, when we have phase changes in the perturbation, the system exhibits chaotic behavior and can be stabilized by exercising greater control over it [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we showed that the strength of the control could be significantly reduced by applying a perturbation with a phase difference between the perturbing signal and the sawtooth signal. Moreover, when we have phase changes in the perturbation, the system exhibits chaotic behavior and can be stabilized by exercising greater control over it [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…We propose to equip the Boost Chopper in DCM with an LQR controller with parameters , and which were initially equipped with a conventional PID corrector. The 2nd order differential equation obtained by inverse Laplace transformation is established respectively by (16) , (17) [ 26 ]: …”
Section: Methods and Toolsmentioning
confidence: 99%
“…[ 24 , 25 ] significantly reduced the THD to 2.82 %, compared with 3.12 % for control using the hysteresis approach. As regards the Buck chopper class [ 26 , 27 ], established the basis for optimizing control using the PID/LQR controller. The comparative study carried out between the analog and digital domains by discretizing the system's closed-loop transfer functions resulted in a perfect juxtaposition of the system's responses in these different domains.…”
Section: Introductionmentioning
confidence: 99%
“…Relation (4) corresponds to the linearised model of defined in [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Modelling Duty Cycle Modulatormentioning
confidence: 99%
“…This technique allows efficient control of the inverter switches supplying the ASM. SRCM has several advantages [8][9][10][11][12][13][14][15][16][17][18][19][20] such as hardware simplicity, low implementation cost, attractive modulation properties, self-modulation and simple design of good quality inverters. MRC was initially introduced for industrial instrumentation applications, such as analogue-to-digital conversion (ADC) [21], digital-to-analogue conversion (DAC) [22] and analogue signal transmission [23].…”
Section: Introductionmentioning
confidence: 99%